2023
DOI: 10.1111/bjh.18714
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to COVID‐19 booster vaccinations in intensively anti‐CD38 antibody treated patients with ultra‐high‐risk multiple myeloma: results from the Myeloma UK (MUK) nine OPTIMUM trial

Sian E. Faustini,
Andrew Hall,
Sarah Brown
et al.

Abstract: Summary Multiple myeloma (MM) and anti‐MM therapy cause profound immunosuppression, leaving patients vulnerable to coronavirus disease 2019 (COVID‐19) and other infections. We investigated anti‐severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) antibodies longitudinally in ultra‐high‐risk patients with MM receiving risk‐adapted, intensive anti‐CD38 combined therapy in the Myeloma UK (MUK) nine trial. Despite continuous intensive therapy, seroconversion was achieved in all patients, but required a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Secondly, although anti-S and T-IGRA values defining a positive antibody or T-cell response were based on historically established thresholds, the absolute values that correlate with clinical protection from COVID-19 remain unclear. Thirdly, current Omicron variants of concern (VOC) have changed; however, a recent report has found that in heavily treated MM patients, multiple doses of vaccine-induced IgG anti-S antibody cross-reacted well with a range of variants 15. Therefore, our findings remain relevant to all MM patients in the present climate with current VOC.…”
mentioning
confidence: 75%
“…Secondly, although anti-S and T-IGRA values defining a positive antibody or T-cell response were based on historically established thresholds, the absolute values that correlate with clinical protection from COVID-19 remain unclear. Thirdly, current Omicron variants of concern (VOC) have changed; however, a recent report has found that in heavily treated MM patients, multiple doses of vaccine-induced IgG anti-S antibody cross-reacted well with a range of variants 15. Therefore, our findings remain relevant to all MM patients in the present climate with current VOC.…”
mentioning
confidence: 75%
“…The stability of nanoparticles can be achieved by adjusting preparation methods and adding surface modifiers. In the preparation process, the size, morphology, and dispersion of nanoparticles can be controlled by solvent precipitation or the co-precipitation method to ensure their stability [155]. Also, using the right surface modifiers, like polyvinylpyrrolidone (PVP), can make nanoparticles more stable and stop them from being cleared out of the bloodstream and breaking down in living things [156].…”
Section: Stability and Biocompatibility Of Nanoparticlesmentioning
confidence: 99%
“…2,[5][6][7][8] Thus, vaccines against SARS-CoV-2 have become the most important preventive strategy to protect these patients from severe complications deriving from SARS-CoV-2 infections. 9 However, MM patients may develop lower antibody responses to anti SARS-CoV-2 vaccines, particularly after anti-CD38 and anti-B-cell maturation antigen (BCMA) drugs [10][11][12][13][14][15][16][17][18] or transplant/CAR-T procedures. [19][20][21][22][23] Therefore they remain at higher risk of breakthrough infections (13%-15%), compared to non-cancer patients (approximatively 4%), that are linked to still significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%